257 Effects of Increasing Dietary Concentrations of High Protein Distillers Dried Grains (HP-DDG) on Growth Performance of Nursery Pigs. (10th April 2018) - Yang, Z; Urriola, P E; Hilbrands, A M; Johnston, L J; Shurson, G C
Abstract: The objective of this study was to use recently-determined ME and SID values of amino acids in a novel high protein distillers grains (HP-DDG; PureStream 40, Lincolnway Energy LLC., Nevada, IA) to determine the effects of increasing concentrations of HP-DDG in Phase 2 and Phase 3 diets on growth performance of nursery pigs. Weaned pigs (n = 360; BW= 6.79 ± 0.02 kg) were blocked by sex and BW, and randomly assigned within block to one of four dietary treatments (9 pigs/pen, 10 pens/treatment). Dietary treatments provided 0, 10, 20, or 30% HP-DDG in diets during Phases 2 (d 7 - 21) and 3 (d 21 - 42) of a 3-phase nursery feeding program. Diets within each phase were formulated to contain equal concentrations of ME, standardized ileal digestible Lys, Met, Thr, and Trp, calcium, standardized total tract digestible phosphorus, vitamins and minerals. During Phase 2, ADG, ADFI, and G:F were linearly reduced as the inclusion rate of HP-DDG increased ( P < 0.01). Similarly in Phase 3, increasing concentrations of HP-DDG depressed ADG, ADFI, and G:F linearly ( P < 0.01). Overall ADG (0.47, 0.44, 0.41, and 0.38 kg), ADFI (0.68, 0.67, 0.62, and 0.59 kg), and G:F (0.70, 0.67, 0.66, and 0.65) of nursery pigs were negatively affected ( P < 0.05) by increasing concentrations of HP-DDG in these diets. Although no differences in morbidity were observed throughout the experiment, including HP-DDG in diets tended to decrease mortality in nursery pigs ( P = 0.07) under a Streptococcus suis and Escherichia coli disease challenge. The reduction in growth performance of pigs fed HP-DDG may be attributed to excessive branched-chain amino acids (BCAA) in the HP-DDG diets. The SID Leu to Lys ratios for 0, 10, 20, and 30% HP-DDG diets were 119, 137, 156, and 173% in Phase 2 diets and 120, 131, 143, and 160% in Phase 3 diets. The SID Ile to Lys ratios ranged from 60 to 69% in Phase 2 diets and 54 to 59% in Phase 3 diets. The SID Val to Lys ratios ranged from 63 to 79% in Phase 2 diets and 64 to 68% in Phase 3 diets. Excessive amounts of Leu in diets may cause BCAA antagonism with Val and Ile which may reduce growth. Further research is needed to determine optimal BCAA to Lys ratios when feeding high dietary inclusion rates of this new generation HP-DDG source.